The Investigation of the effects of deep dry needling into trigger points of temporalis, sternocleidomastoid and upper trapezius on females with episodic tension type headache - Abaschian, Faezeh; Mansoursohani, Soheil; Togha, Mansoureh; Yassin, Marzieh; Abadi, Laleh (Researcher Bulletin of Medical Sciences, 2021)
Introduction: Tension type headache is the most common type of headache that is associated with myofascial pain syndrome and trigger points. The aim of this study was to evaluate the efficacy of deep dry needling into trigger points of temporalis, sternocleidomastoid and upper trapezius muscles of females with episodic tension type headache. Materials and Methods: The study was a clinical randomized, single-blind, parallel-group trial in which 24 participants were allocated into two groups. The first group received dry needling with passive stretching treatment and the second group (control group) received only passive stretching. Subjects were asked to record headache indices (headache intensity and frequency) for 4 weeks before treatment. Headache intensity and frequency and quality of life (SF-36) were measured at baseline and 4 weeks after the intervention. Results: In the dry needling group, the intensity and frequency of headache and physical functioning scores of quality of life questionnaire were significantly improved after treatment (p <0.05). Conclusion: Due to the positive effects of deep dry needling and passive stretching in females with episodic tension type headache, the use of deep dry needling into trigger points of head and neck musculature is recommended in the presence of episodic tension type headache.